When Does Inflation Hurt Economic Growth? Different Nonlinearities for Different Economies - Richard C.K. Burdekin; Arthur T. Denzau; Manfred W. Keil; Thitithep Sitthiyot; Thomas D. Willett (Claremont McKenna College, Department of Economics, 2000)
We show that the effects of inflation on growth change substantially as the inflation rate rises. Moreover the nonlinearities are quite different for industrial economies than for developing countries. We find that the threshold at which inflation first begins to seriously negatively affect growth is around 8% for industrial economies but 3% or less for developing countries. Marginal growth costs for developing countries then decline significantly above 50% inflation. Failure to account for nonlinearity biases downward the estimated effects of inflation on growth. Mixing industrial and developing economies together also produces unreliable results.
Keywords: O4; E6; C1; 330; inflation; growth; non-linearity